Consumptive Decision-Making of Santri in Using Personal Shopping Services (Jastip) at Islamic Boarding Schools: A Phenomenological Study - Muhammad Daffa’ Fawwazy; Moh. Riyadi; Noufal Jamil (CV Edujavare Publishing, 2026)
The emergence of personal shopping services (jastip) in Islamic boarding schools (pesantren) has become a practical solution to the limited access of students (santri) to goods outside the boarding school environment. However, this convenience not only facilitates the fulfillment of daily needs but also has the potential to encourage consumptive behavior. This study aims to analyze how the phenomenon of jastip shapes the consumptive behavior of santri, examine the decision-making process underlying their use of jastip within the context of the simplicity values upheld in pesantren, and explore the meaning of jastip from the perspective of the students. This study employed a qualitative approach with a phenomenological design. Five santri were selected as research informants using purposive sampling. Data were collected through observation, semi-structured interviews, and documentation, and were analyzed using data reduction, data display, and conclusion drawing, while data credibility was ensured through source triangulation. The findings reveal that jastip has become the primary alternative for obtaining goods unavailable within the pesantren. The ease of access provided by jastip also increases the likelihood of consumptive behavior, influenced by peer groups, consumption trends, and the convenience of acquiring products. Nevertheless, most participants considered product usefulness, financial capability, and the values of simplicity before making purchasing decisions. From the perspective of the Theory of Planned Behavior, the consumptive decision-making process of santri is influenced by attitudes toward the use of jastip, subjective norms derived from the social environment, and perceived behavioral control reflected in their ability to regulate spending. This study concludes that jastip plays a dual role: it serves as an effective means of fulfilling students' needs while simultaneously creating the potential for consumptive behavior if not accompanied by adequate self-control and the internalization of the values of simplicity promoted within the pesantren environment.